Design and fabrication of 3D printed sandwich core structure - Han, Yiqian (Nanyang Technological University, 2023)
Cellular structure in sandwich structures have significant benefits in achieving optimal mechanical performance with high strength to weight ratio. Advanced technology, additive manufacturing or 3D printing, has enabled both the flexibilities in designing of parts and the ease of alternating structural design such as sandwich structure. The mechanical strength of the sandwich structure can be enhanced by 3D printing the honeycomb core in various alternative cellular shapes as part of the redesign process. With 3D printing technology, the conventional adhesives used between the face sheets and the core structure was eliminated completely. This will also reduce production time and cost which will be favorable to the industry. This project focused on mainly three core shapes, namely, hexagon shaped, cross shaped and triangle shaped core structures. The redesigned core structure was printed together with the face sheets to complete the sandwich structure. Mechanical testing such as 3-point bending test was conducted on these specimens to find out the mechanical strength among the three core shapes. The cross-shaped core structure exhibited the highest mechanical strength, capable of withstanding bending forces up to 419.0 N, followed by the hexagonshaped core structure at 352.3 N, and finally the triangle-shaped core structure at 274.9 N. These specimens were then subjected to CT scan imaging to evaluate any internal damagethe results generated, it was concluded that the sandwich structure with the cross shaped core showed the best and highest strength among the other two core shapes.